2021
DOI: 10.4274/jcrpe.galenos.2020.2020.0149
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenital Central Hypothyroidism Caused by a Novel Variant (Gln1255Ter) in <i>IGSF1</i> Gene

Abstract: Loss-of-function mutations in the immunoglobulin superfamily, member 1 ( IGSF1 ) gene cause X-linked central hypothyroidism, and therefore its mutation affects mainly males. Central hypothyroidism in males is the hallmark of the disorder, however some patients additionally present with hypoprolactinemia, transient and partial growth hormone deficiency, early/normal timing of testicular enlargement but delayed testosterone rise in puberty, and adult macro-orchidism. Here, we report a boy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Using current criteria for GHD, this was reported in 16% of children in IGSF1 deficiency ( 3 , 4 ), but in all cases GHD was transient. Similarly, a recently published Turkish patient with IGSF1 deficiency was treated with GH for two years, but during adolescence his GHD proved transient ( 21 ). Remarkably, in adult IGSF1 deficient patients IGF-1 levels are generally in the upper half or even above the reference range, with increased GH secretion and variable mild acromegalic features in late adulthood ( 3 , 4 , 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…Using current criteria for GHD, this was reported in 16% of children in IGSF1 deficiency ( 3 , 4 ), but in all cases GHD was transient. Similarly, a recently published Turkish patient with IGSF1 deficiency was treated with GH for two years, but during adolescence his GHD proved transient ( 21 ). Remarkably, in adult IGSF1 deficient patients IGF-1 levels are generally in the upper half or even above the reference range, with increased GH secretion and variable mild acromegalic features in late adulthood ( 3 , 4 , 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…A TRH test may be helpful in this context to differentiate hypothalamic and pituitary origins [13], although the value of TRH tests in pituitary assessments is debatable [13, 18], and as was the case here, variable results have been reported in IGSF1 deficiency [9, 19-27].…”
Section: Discussionmentioning
confidence: 99%
“…As thyroid hormones are critical for the development of the central nervous system, Individuals with CCH may result in developmental delay due to untreated neonatal hypothyroidism. 8 The underlying molecular basis of CCH is poorly understood, although the genetic studies have been reported in a few cases. [7][8][9][10][11][12] At present, genetic defects in only four genes (TSHB, TRHR, IGSF1 and the TBL1X) have been identified in patients with isolated CCH.…”
Section: Introductionmentioning
confidence: 99%
“…8 The underlying molecular basis of CCH is poorly understood, although the genetic studies have been reported in a few cases. [7][8][9][10][11][12] At present, genetic defects in only four genes (TSHB, TRHR, IGSF1 and the TBL1X) have been identified in patients with isolated CCH. 12 Here, we investigate the genetic mechanisms in seven patients with CCH by chromosomal microarray analysis (CMA) and whole-exome sequencing (WES).…”
Section: Introductionmentioning
confidence: 99%